A study on the influences of customers' characteristics in spending trends among rural and urban area / Nor Amira Muhamad and Noor Atiqah Muhammad Ghozali - Muhamad, Nor Amira; Muhammad Ghozali, Noor Atiqah (2013)
The purpose of this study was about the influences of customers' characteristics in spending trends among rural and urban area. The researchers want to identify the influences in spending trends and to determine the relationship between customers' characteristics and their spending trends. The questionnaire is the method that being used by researchers to collect data. The population of this study is 167 which consist of two areas. The two areas are rural and urban. For rural, researchers choose Taman Jengka Mahkota at Bandar Jengka, Pahang while for urban researchers choose Taman Kantan Permai at Kajang, Selangor. Based on the research finding, the researchers found that the customers' characteristics in spending trends are Psychological, Personal, Social and Cultural. The Social characteristic was the highest among the other characteristics. Lastly, the researchers found that the customers' characteristic has no relationship with their spending trends. As the conclusion, the researchers summarized that most of the respondents spending their money by socializing because of the rapid change of technology contribute them to purchase online and at the same time going out with families, friends, peers, and colleagues to spend their money. As recommendations for future research, the researchers recommend to increase the size of respondents' population, involve respondents from pure rural area community and no limited time for questionnaire distribution.